PERTUMBUHAN dan PRODUKSI TIGA VARIETAS TANAMAN PAK CHOY (BRASSICA CHINENSIS L.) PADA BERBAGAI NILAI ELECTRICAL CONDUCTIVITY LARUTAN HIDROPONIK. - Nurkhotimah, Sjarif Avitijadi Adimihardja (Jurnal Pertanian, 2011)
Pak Choy is one of the economic valuable vegetables in Indonesia. Thisresearch was aimed to increase the growth and productivity of three varieties of PakChoi through the variation of electrical conductivity (EC) rates in the hydroponicsolution. The complete randomized factorial was used in ths research. They were threevarieties of he variety of Pak Choy (V1 is Green, V2 is Green Fut Choi, V3 is GreenFortune) and four EC rates {1.5 (E1), 2.0 (E2), 2.5 (E3), 3.0 (E4) mS/cm}. The varietyof Pak Choy gave significant differentiation to all of the affect to the numbers of leaves,root length and the numbers of chlorophylls. The regression analisys was showed thatincreasing of the mg EC rates would increase the number of chlorophylls of all PakChoi varieties. The interaction between Pakchoi varieties and the EC rates show incanopy diametesr, that the combination in V2, differences were found in E4 and E2 andthe best value was found in V2E4 at 10 DAP (Day After Planted). In 15 DAP, canopydiameters in V2 and V3 were not different. In V1, differences were found among E1,E2, and E4. The best value was found in V2E3 at 15 DAP.